Analisa dan Implementasi Kriptografi File Dokumen Dengan Metode Algoritma Advanced Encryption Standard (AES) Berbasis Web (Studi Kasus: CV. Prima Glanze Utama) - Riyan Wahyu Pratama; Teti Desyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Security and confidentiality when exchanging data and information are very important in the current era of information and communication technology, therefore a branch of science has been developed that studies ways to secure data or known as cryptography. There are quite a number of algorithmic methods in cryptography, one of which is the Advanced Encryption Standard (AES) algorithm, which is a cryptographic algorithm that can be used to secure data. With the implementation of a cryptographic system so as to reduce the possibility of a data security crime risk because messages or files and documents are protected. The results obtained from this study are the implementation of a document file cryptography system using the Advanced Encryption Standard (AES) algorithm method and then processed, so that the system can perform encryption and decryption.